Racial theories in fascist Italy - Gillette, Aaron, 1964- (Routledge studies in modern European history, 2002)
Racial Theories in Fascist Italy examines the role played by race and racism in the development of Italian identity during the fascist period. The book examines the struggle between Mussolini, the fascist hierarchy, scientists and others in formulating a racial persona that would gain wide acceptance in Italy. This book will be of interest to historians, political scientists concerned with the development of fascism and scholars of race and racism.